2020
DOI: 10.1159/000508983
|View full text |Cite
|
Sign up to set email alerts
|

Precision Nephrology Is a Non-Negligible State of Mind in Clinical Research: Remember the Past to Face the Future

Abstract: CKD is a major public health problem. It is characterized by a multitude of risk factors that, when aggregated, can strongly modify outcome. While major risk factors, namely, albuminuria and low estimated glomerular filtration rate (eGFR) have been well analyzed, a large variability in disease progression still remains. This happens because (1) the weight of each risk factor varies between populations (general population or CKD cohort), countries, and single individuals and (2) response to nephroprotective dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 108 publications
(149 reference statements)
0
25
0
Order By: Relevance
“…Considering CKD as a risk equivalent has generated many debates, because it would be translated into clinical practice in an aggressive pharmacological treatment (e.g., extensive use of statins) to all patients with CKD irrespective of age, gender, eGFR, albuminuria levels, or renal diagnoses. Conversely, a more careful approach to CV risk in CKD has been prompted by the International Society of Nephrology, and consists of improving the knowledge of biomarkers that would allow to better forecast CV events [77]. Metalloproteinases may be the true candidate for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Considering CKD as a risk equivalent has generated many debates, because it would be translated into clinical practice in an aggressive pharmacological treatment (e.g., extensive use of statins) to all patients with CKD irrespective of age, gender, eGFR, albuminuria levels, or renal diagnoses. Conversely, a more careful approach to CV risk in CKD has been prompted by the International Society of Nephrology, and consists of improving the knowledge of biomarkers that would allow to better forecast CV events [77]. Metalloproteinases may be the true candidate for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…To this aim, the past two decades have been signed by the implementation of clinical trials testing the efficacy of novel drugs on cardiovascular and renal protection in CKD patients. 72 This was a really great effort in clinical research. A first crucial step was the demonstration that drugs inhibiting the Renin-Angiotensin-Aldosterone-System (RAASi) are effective in reducing both the eGFR decline over time and CV risk.…”
Section: Peripheral Artery Disease In Chronic Kidney Disease: Future mentioning
confidence: 99%
“…Clinicians need to be able to rely on SRs, allowing them to select a RPM that is applicable in the context of their individual patient. As in other populations, finding robust RPMs that can be personalized according to the setting is a major challenge [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only one review [ 21 ] reported clearly on the initial number of variables that were considered in each development model. The model performance of individual risk prediction models [ 28 ] can be assessed by evaluating calibration or predicted vs observed probability e.g. by using calibration plot, calibration slope, or Hosmer-Lemeshow test, and by evaluating discrimination or the ability to distinguish patients with AKI from those who do not have AKI, which is usually done by providing the c statistic with a confidence interval.…”
Section: Discussionmentioning
confidence: 99%